The MetaCyc database of metabolic pathways and enzymes. Issue Volume 46:Issue D1(2018) (20th October 2017) - Caspi, Ron; Billington, Richard; Fulcher, Carol A; Keseler, Ingrid M; Kothari, Anamika; Krummenacker, Markus; Latendresse, Mario; Midford, Peter E; Ong, Quang; Ong, Wai Kit; Paley, Suzanne; Subhraveti, Pallavi; et al.
Abstract: MetaCyc (https://MetaCyc.org ) is a comprehensive reference database of metabolic pathways and enzymes from all domains of life. It contains more than 2570 pathways derived from >54 000 publications, making it the largest curated collection of metabolic pathways. The data in MetaCyc is strictly evidence-based and richly curated, resulting in an encyclopedic reference tool for metabolism. MetaCyc is also used as a knowledge base for generating thousands of organism-specific Pathway/Genome Databases (PGDBs), which are available in the BioCyc (https://BioCyc.org ) and other PGDB collections. This article provides an update on the developments in MetaCyc during the past two years, including the expansion of data and addition of new features.